CREPT/RPRD1B, a Recently Identified Novel Protein Highly Expressed in Tumors, Enhances the β-Catenin·TCF4 Transcriptional Activity in Response to Wnt Signaling - Zhang, Yanquan (American Society for Biochemistry and Molecular Biology, 2014)
CREPT (cell cycle-related and expression elevated protein in tumor)/RPRD1B (regulation of nuclear pre-mRNA domain-containing protein 1B), highly expressed during tumorigenesis, was shown to enhance transcription of CCND1 and to promote cell proliferation by interacting with RNA polymerase II. However, which signaling pathway is involved in CREPT-mediated activation of gene transcription remains unclear. In this study, we reveal that CREPT participates in transcription of the Wnt/β-catenin signaling activated genes through the β-catenin and the TCF4 complex. Our results demonstrate that CREPT interacts with both β-catenin and TCF4, and enhances the association of β-catenin with TCF4, in response to Wnt stimulation. Furthermore, CREPT was shown to occupy at TCF4 binding sites (TBS) of the promoters of Wnt-targeted genes under Wnt stimulation. Interestingly, depletion of CREPT resulted in decreased occupancy of β-catenin on TBS, and over-expression of CREPT enhances the activity of the β-catenin·TCF4 complex to initiate transcription of Wnt target genes, which results in up-regulated cell proliferation and invasion. Our study suggests that CREPT acts as an activator to promote transcriptional activity of the β-catenin·TCF4 complex in response to Wnt signaling.